2000
DOI: 10.1046/j.1471-4159.2000.751283.x
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Directed Mutations in the Third Intracellular Loop of the Serotonin 5‐HT1A Receptor Alter G Protein Coupling from Gi to Gs in a Ligand‐Dependent Manner

Abstract: Abstract:The effect of mutations (V344E and T343A/ V344E) in the third intracellular loop of the serotonin 5-HT 1A receptor expressed transiently in human embryonic kidney 293 cells have been examined in terms of receptor/G protein interaction and signaling. Serotonin, (R)-8-hydroxy-2-dipropylaminotetralin [(R)-8-OH-DPAT], and buspirone inhibited cyclic AMP production in cells expressing native and mutant 5-HT 1A receptors. Serotonin, however, produced inverse bell-shaped cyclic AMP concentration-response curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 20 publications
(28 reference statements)
2
25
1
Order By: Relevance
“…Likewise, 5-HT1A-i2 loop peptides mediate direct coupling to inhibition of cAMP (Varrault et al, 1994). Mutation of Ci3 residues (V344E and T343A/V344E) enhanced receptor coupling to G s over G i , consistent with its role in determining G␣ i specificity (Malmberg and Strange, 2000). Thus, whereas Ci3 seems to mainly dictate G␣ i specificity, our results indicate that Ci2 is mainly implicated in G␤␥ signaling but also contributes to G␣ i signaling.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Likewise, 5-HT1A-i2 loop peptides mediate direct coupling to inhibition of cAMP (Varrault et al, 1994). Mutation of Ci3 residues (V344E and T343A/V344E) enhanced receptor coupling to G s over G i , consistent with its role in determining G␣ i specificity (Malmberg and Strange, 2000). Thus, whereas Ci3 seems to mainly dictate G␣ i specificity, our results indicate that Ci2 is mainly implicated in G␤␥ signaling but also contributes to G␣ i signaling.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, coactivation of G s by D1 receptor activation was required to observe DPAT-induced potentiation. This enhancement of D1 response was blocked by pertussis toxin treatment, indicating that the potentiation is mediated by G i /G o proteins and is not due to weak agonist-mediated stimulation of G s , as observed for mutants of the 5-HT1A Ci3 domain (Malmberg and Strange, 2000). DPAT-induced potentiation was greatest for the P150T-5-HT1A receptor, which lacked coupling to adenylyl cyclase II.…”
Section: Substitutionmentioning
confidence: 67%
See 1 more Smart Citation
“…Then a putative G protein-binding site is clearly shown by an arrangement, in which the iLP1 ( Figures 6A and B (red)) is located above the iLP3 (Figures 6and B (blue)), which forms a bed, and the iLP2 (Figures 6 A and B (yellow)) is set towards the back of the proposed pocket ( Figure 6C). This pocket, which is formed by the three loops, is consistent with the previous reports suggesting that more than one intracellular loop are involved in the contact with the G protein through mutagenesis studies [13,[15][16][18][19]38]. The putative pocket is further supported by the presence of the key residues, which are important to the G protein coupling identified by mutagenesis, including R60 in the iLP1 [31], R130 and F138 in the iLP2 [38,20], and C223 in the iLP3.…”
Section: Putative G Protein-binding Pocket Formed By the Three Intracsupporting
confidence: 92%
“…Recombinant protein studies have implied that the N-and C-terminal portions of the third intracellular loop (iLP3), and the cytoplasmic tail of the receptors are involved in the G protein activation and signal transduction. Other studies have shown that in the second intracellular loop (iLP2), the membrane-proximal portions of the iLP3, and the N-terminal segment of the cytoplasmic tail both contain amino acids which have been predicted to play a role in regulating the selectivity of G protein and GPCR interactions [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%